1978
DOI: 10.1159/000144943
|View full text |Cite
|
Sign up to set email alerts
|

Post-hatching evolution of the pineal gland of the chicken

Abstract: The authors studied the evolution of the pineal gland of the chicken (Gallusgallus) from hatching until 34 months of age. They describe the progressive decrease of the follicular cavities and the appearance of solid-looking cavities. The stroma increases with age, dividing the pineal parenchyma into territories of small caliber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 4 publications
6
20
1
Order By: Relevance
“…Relatively little attention has been directed toward this type of avian pinealocyte (Vollrath 1981). Boya and Calvo (1980) consider that chicken parafollicular cells represent the same type of cells as the follicular cells, although there is no clearcut structural polarization. Ohshima and Matsuo (1988) have suggested that the parafollicular cell of the chicken pineal organ is a type of pinealocyte, because of the occasional presence of granular vesicles and synaptic ribbons, although they have not found a bulbous protrusion carrying a sensory cilium.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little attention has been directed toward this type of avian pinealocyte (Vollrath 1981). Boya and Calvo (1980) consider that chicken parafollicular cells represent the same type of cells as the follicular cells, although there is no clearcut structural polarization. Ohshima and Matsuo (1988) have suggested that the parafollicular cell of the chicken pineal organ is a type of pinealocyte, because of the occasional presence of granular vesicles and synaptic ribbons, although they have not found a bulbous protrusion carrying a sensory cilium.…”
Section: Discussionmentioning
confidence: 99%
“…The parenchyma consists of numerous small follicles. The pineal stalk of adult chicken is very short; in general, the parenchyma has a compact appearance and thus resembles the glandular structure of the mammalian pineal (Boya and Calvo, 1978). In adult Japanese quail the pineal stalk is thin and long and the parenchyma is follicular, arranged around very narrow lumen.…”
Section: Transformation Of Avian Pineal Organ From Photosensory To Enmentioning
confidence: 99%
“…These types differ not only in the architecture and cellular organization, but also in the afferent and efferent innervation. Moreover, the structure and innervation of the avian pineal organ undergo significant changes during postembryonic life as it has been described in the chicken, Japanese quail and turkey (Boya and Calvo 1978, 1979, 1980, Ohshima and Matsuo 1984, Sato and Wake 1984, Ohshima and Hiramatsu 1993, Przybylska-Gornowicz et al 2005. It is reasonable to expect that such a great variability in the pineal morphology reflects in significant differences in the processes controlling MLT secretion.…”
Section: Introductionmentioning
confidence: 96%
“…It represents several morphological types -from the saccular type through the tubulo-follicular form to the solid-follicular one (Boya and Calvo 1978, Vollrath 1981, Ohshima and Hiramatsu 1993, Prusik 2005, Przybylska-Gornowicz et al 2005, Prusik et al 2006, Prusik and Lewczuk 2008a. These types differ not only in the architecture and cellular organization, but also in the afferent and efferent innervation.…”
Section: Introductionmentioning
confidence: 99%